The burden of atopic dermatitis: its impact on family psychosocial functioning - Aleksandra Kobusiewicz; Anna Zalewska-Janowska (Termedia Publishing House, 2023)
Atopic dermatitis (AD) is one of the most common childhood dermatological diseases. Its characteristic clinical feature is intractable pruritus, which causes an urge to scratch the skin, and the occurrence of skin lesions which are typical in their morphology and location. It is characterised by its chronicity, difficulty of treatment and numerous psychosocial consequences which affect not only the patient, but also all family members. The child's severe pruritus and visible skin lesions result in sleep disturbances, chronic fatigue, difficulties in intra- and extra-familial relationships or problems in the family's financial situation. The effectiveness of treatment provided is highly dependent on the parents' commitment, knowledge and skills, as well as their mental condition. Caring for a child with AD is demanding and disrupts many aspects concerning the quality of family life. This article addresses the impact of AD on child and family functioning and the burden of the disease.